Serum levels of enclomiphene and zuclomiphene in men with hypogonadism on long‐term clomiphene citrate treatment. (11th September 2016) - Helo, Sevann; Mahon, Joseph; Ellen, Joseph; Wiehle, Ron; Fontenot, Gregory; Hsu, Kuang; Feustel, Paul; Welliver, Charles; McCullough, Andrew
Abstract : Objectives: To determine the relative concentrations of enclomiphene (ENC) and zuclomiphene (ZUC) isomers in men with hypogonadism on long‐term clomiphene citrate (CC) therapy, and to determine whether patient age, body mass index (BMI) or duration of therapy were predictive of relative concentrations of ENC and ZUC. Patients and methods: Men already receiving CC 25 mg daily therapy for secondary hypogonadism for a minimum of 6 weeks were recruited to have their ENC and ZUC levels assessed. Total testosterone, free testosterone, oestradiol, follicle stimulating hormone (FSH), and luteinizing hormone (LH) before initiation of and while on CC therapy were recorded for all patients. Patient demographics including age, BMI and medical comorbidites were recorded. Serum samples were obtained at the time of enrolment to determine ENC and ZUC concentrations. Results: A total of 15 men were enrolled in the period from June 2015 to August 2015. The median (range) patient age was 36 (22–70) years, BMI 32.0 (21.1–40.3) kg/m 2 and duration of treatment 25.9 (1.7–86.6) months. Baseline median total testosterone, oestradiol and LH levels were 205.0 ng/dL, 17.0 pg/mL and 4.0 mlU/mL, respectively. The post‐treatment median total testosterone, oestradiol and LH level increased to 488.0 ng/dL, 34.0 pg/mL and 6.1 mIU/mL, respectively (all P <0.001). The median ENC and ZUC concentrations were 2.2 and 44.0 ng/mL, respectively. After at least 6 weeks of CC therapy, the median ZUC: ENC serum concentration ratio was 20:1. On linear regression analysis. patient age, BMI, duration of treatment and serum testosterone levels were not predictive of ENC or ZUC concentrations. Conclusions: Long‐term CC therapy resulted in a significant alteration of ENC and ZUC concentrations, with ZUC as the predominant isomer. Given the vastly different biochemical and toxicological properties of ENC and ZUC, this study supports the need for the development of a pure selective oestrogen receptor antagonist for the treatment of men with hypogonadism.